2006
DOI: 10.1097/01.mol.0000217895.67444.de
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants predisposing to cardiovascular disease

Abstract: During the last year, tremendous effort has been made in elucidating new genes associated with cardiovascular disease predisposition. For the most part, however, major breakthroughs have not been made, primarily due to the poor replication of results among studies, as a consequence of poor experimental design. Nevertheless, we have increased our understanding of the complexity of cardiovascular disease and the relevance of gene-environment interactions as the ultimate drivers of the individual predisposition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 131 publications
0
34
0
Order By: Relevance
“…It is now essential to establish whether alterations of the class IIa HDAC-MEF2 axis occur in these human pathologies. Genetic alterations of MEF2 family members have been linked to cardiovascular diseases (Wang, 2005;Visvikis-Siest and Marteau, 2006) and acute lymphoblastic leukemia (Yuki et al, 2004;Prima et al, 2005). Similarly, alterations of MEF2 transcriptional activity have been implicated in neurodegenerative disorders (Camins et al, 2006) and cardiac hypertrophy (Czubryt and Olson, 2004).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…It is now essential to establish whether alterations of the class IIa HDAC-MEF2 axis occur in these human pathologies. Genetic alterations of MEF2 family members have been linked to cardiovascular diseases (Wang, 2005;Visvikis-Siest and Marteau, 2006) and acute lymphoblastic leukemia (Yuki et al, 2004;Prima et al, 2005). Similarly, alterations of MEF2 transcriptional activity have been implicated in neurodegenerative disorders (Camins et al, 2006) and cardiac hypertrophy (Czubryt and Olson, 2004).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…For decades, Apo E has been regarded as one of the important factor of lipoprotein genetics [9,10]. Several studies have demonstrated the impact of Apo E polymorphisms in cerebrovascular and cardiovascular diseases in a reproducible fashion.…”
mentioning
confidence: 99%
“…These interactions have made it difficult to establish a universally accepted mechanism of atherogenesis (Peltonen & McKusick, 2001), because the sample sizes needed to test these gene-gene and gene-environment interactions are much larger than those needed for simpler genotype-phenotype associations (Ordovas & Shen, 2002). Pathways that trigger atherosclerosis in the general population have yet to be elucidated (Visvikis-Siest & Marteau, 2006). Most genomic scale experiments have compared either full-blown plaques against non-affected aortic segments (Archacki et al, 2003;Forcheron et al, 2005;Hiltunen et al, 2002;Shanahan et al, 1997), or they have analyzed differences between ruptured and unruptured plaques (Adams et al, 2006;Faber et al, 2001;Papaspyridonos et al, 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Markers do not necessarily cause the disease, but can be used to improve diagnosis and risk assessment (Gibbons et al, 2004). Inflammatory markers such as C-reactive protein (CRP) factors [Tsimikas et al, 2006;Ridker, 2000] plus markers of oxidative damage such as myeloperoxidase (Shao et al, 2006) and paraoxanase (Visvikis-Siest & Marteau, 2006) have already increased clinicians' predictive power. As more markers of atherosclerosis are correlated with disease progression and outcome, the genetic variation contributing to predisposition and initial manifestation will become clear.…”
Section: Introductionmentioning
confidence: 99%